Susceptibility of Two Southern Ocean Phytoplankton Key Species to Iron Limitation and High Light - Trimborn, Scarlett; Thoms, Silke; Bischof, Kai; Beszteri, Sara (Frontiers in Marine Science, 2019)
Although iron (Fe) availability primarily sets the rate of phytoplankton growth and primary and export production in the Southern Ocean, other environmental factors, most significantly light, also affect productivity. As light availability strongly influences phytoplankton species distribution in low Fe-waters, we investigated the combined effects of increasing light (20, 200 and 500 μmol photons m−2 s−1) in conjunction with different Fe (0.4 and 2 nM Fe) availability on the physiology of two ecologically relevant phytoplankton species in the Southern Ocean, Chaetoceros debilis (Bacillariophyceae) and Phaeocystis antarctica (Haptophyceae). Fe-deficient cells of P. antarctica displayed similar high growth rates at all irradiances. In comparison, Fe-deplete C. debilis cells grew much slower under low and medium irradiance and were unable to grow at the highest irradiance. Interestingly, Fe-deficient C. debilis cells were better protected against short-term excessive irradiances than P. antarctica. This tolerance was apparently counteracted by strongly lowered growth and particulate organic carbon production rates of the diatom relative to the prymnesiophyte. Overall, our results show that P. antarctica was the more tolerant species to changes in the availability of Fe and light, providing it a competitive advantage under a high light regime in Fe-deficient waters as projected for the future.